Malignant Oral Lesions in Sulaimania Governorate/ a (5 Years) Retrospective Study - Khudier , Hassanain H (Diyala Journal of Medicine, 2019)
Background: Cancers of the oral cavity and oropharynx represents approximately three percent of all malignancies in men and two percent of all malignancies in women in the United State. Squamous cell carcinoma, which arises from the oral mucosal lining, accounts for 90%- 95% of oral cancer. Objective: aim of this study is to detect oral cancers in Sulaimania and to know what is the most common type and its commonest location in comparism to other studies. Patients&Methods: During the period from 1st Jan. 2004 to 30th June 2009, all histopathological reports in Sulaimani city with diagnosis of oral cancers for patients attended and performing biopsies for suspected oral lesions were included. These biopsies were received, processed and embedded in paraffin, sectioning, then stained by Haematoxylin and Eosin stain. All collected information were analyzed according to age, sex, site and histopathological diagnosis. Results: Oral cancers were diagnosed in 82 out of 665 oral lesions (represented as 12.33% from the total number of oral lesion biopsies).Squamous cell carcinoma (SCC) was the most common type of the malignant neoplasm of oral cavity found in 46 cases (56.1% ).Most frequent cases found in the age distribution range between 50 -70 years with M: F ratio 1.2:1. The most common affected site was the lower lip(39%) followed by the tongue(20%). Malignant neoplasms of salivary glands included 16 cases (19.6%),female 10, male 6 with F:M ratio is 1.66:1. Conclusion: The most common oral cancer in sulaimania is SCC of oral mucosa affecting mainly the old age group, and males affected more than females, and the most common location is the lower lip. The second most common cancer is salivary gland carcinoma and commonest histological type is adenocarcinoma.